P11 DERIVO mini flow diverter device (DmFD): initial clinical experience. (29th August 2022) - Fernando, P; Caballero, G; Graña, M; Fernandez, C; Alvarado, L; Gonzalez, M; Horvath, F; Nazar, F; Galiana, G; Genco, J; Parra, L
Abstract : Background: FD had shown to be effective in excluding different types of vascular pathology (mainly aneurismatic dilation). New generation, low profile FD stents, are allowing treatment of aneurysm/dissection, lying over small, distal parent arteries. Aim: To analyze and report the initial experience using the DmFD. Methods: Between April 2021 and April 2022, 15 patients were prospectively treated using the DmFD. Baseline clinical status, aneurysm morphology/morphometry, intraprocedural technical details, modified Rankin Scale (mRS) at admission/discharge, follow up magnetic resonance imaging and angiographic results after treatment were collected. Results: 15 patients (60% female; mean 42.3yo, range:28–78yo) and 18 aneurysm were embolized, either alone or coil-assisted.10 patients (66.6%) were symptomatic, while 5 (33, 3%) remained asymptomatic. Previous coiling was observed in 2 (11, 1%) cases, and concomitant coiling in 1 (5, 5%). Adverse events included, 1 (5, 5%) guidewire perforation and in-stent thrombosis in 1 (5, 5%). At discharge, 86, 6% and 13, 4% mRS of 0 and 1 respectively, was observed. Median Follow up of 7, 5 months was achieved, by MRI/DSA in 100% of the patients. In MRI, complete occlusion or a small remnant was observed in 77, 7% (14/18) and 11, 1% (2/18), respectively. Complete occlusion OKM D was observed in 83, 3% (15/18) or a small aneurysmal remnant, OKM C1-C3 in 5, 55% (1/18) under DSA. No mortality related case was observed during Follow Up. Conclusion: The DmFD, showed to be safe and effective, with high occlusion rates and low complication adverse events. Longer Follow up and bigger cohorts of patient is needed. References: Bhogal P, Wong K, Uff C, Wadley J, Makalanda Hl. The Silk Vista Baby: Initial Experience and Report of Two Cases. Interv Neuroradiol 2019;25:530–8. 10.1177/15910199198391962. Martínez-Galdámez M, Biondi A, Kalousek V, et al . Periprocedural Safety and Technical Outcomes of the New Silk Vista Baby Flow Diverter for the Treatment of Intracranial Aneurysms: Results from a Multicenter Experience. J Neurointerv Surg 2019;11:723–7. 10.1136/Neurintsurg-2019-014770. Do you have any conflict of interest to declare? : No